Applications of a duality between generalized trigonometric and hyperbolic functions - Miyakawa, Hiroki; Takeuchi, Shingo (arXiv.org, 2020)
It is shown that generalized trigonometric functions and generalized hyperbolic functions can be transformed from each other. As an application of this transformation, a number of properties for one immediately lead to the corresponding properties for the other. In this way, Mitrinović-Adamović-type inequalities, multiple-angle formulas, and double-angle formulas for both can be produced.